2016
DOI: 10.1038/srep36672
|View full text |Cite
|
Sign up to set email alerts
|

Tree species, tree genotypes and tree genotypic diversity levels affect microbe-mediated soil ecosystem functions in a subtropical forest

Abstract: Tree species identity and tree genotypes contribute to the shaping of soil microbial communities. However, knowledge about how these two factors influence soil ecosystem functions is still lacking. Furthermore, in forest ecosystems tree genotypes co-occur and interact with each other, thus the effects of tree genotypic diversity on soil ecosystem functions merit attention. Here we investigated the effects of tree species, tree genotypes and genotypic diversity levels, alongside soil physicochemical properties,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
13
1

Year Published

2018
2018
2020
2020

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(14 citation statements)
references
References 54 publications
0
13
1
Order By: Relevance
“…To explore potential ecological functions in the rhizosphere of each individual tree, we analyzed activities of three important enzymes for C, N, and P acquisition-β-glucosidase (EC 3.2.1.21), N-acetylglucosaminidase (EC 3.1.6.1), and acid phosphatase (EC 3.1.3.2), respectively-in the soil samples, using 4-methylumbelliferone (MUB) derivatives and previously described methodology [15]. To prepare soil slurries, 50 mL of 50 mM sodium acetate buffer (pH 5.5) were added to 0.5 g portions of soil (wet weight, equivalent to 0.098-0.183 g dry weight) and homogenized for 5 min in a bath sonicator.…”
Section: Analysis Of Soil Rhizosphere Enzyme Activitiesmentioning
confidence: 99%
See 1 more Smart Citation
“…To explore potential ecological functions in the rhizosphere of each individual tree, we analyzed activities of three important enzymes for C, N, and P acquisition-β-glucosidase (EC 3.2.1.21), N-acetylglucosaminidase (EC 3.1.6.1), and acid phosphatase (EC 3.1.3.2), respectively-in the soil samples, using 4-methylumbelliferone (MUB) derivatives and previously described methodology [15]. To prepare soil slurries, 50 mL of 50 mM sodium acetate buffer (pH 5.5) were added to 0.5 g portions of soil (wet weight, equivalent to 0.098-0.183 g dry weight) and homogenized for 5 min in a bath sonicator.…”
Section: Analysis Of Soil Rhizosphere Enzyme Activitiesmentioning
confidence: 99%
“…Such microbes must be adapted to both high and low salinity. Potential soil microbial ecological functions were characterized by measuring activities of important soil enzymes for the acquisition of macronutrients such as carbon (C; β-glucosidase), nitrogen (N; N-acetylglucosaminidase), and phosphorus (P; acid phosphatase) [15].…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, recent studies have investigated links between particular groups of organisms, and general relationships between diversity and processes have been found. However, studies either detail microbial diversity across general vegetation, land use or habitat classes (Chen et al, 2015;Flores-Rentería, Rincón, Valladares, & Yuste, 2016;Kaiser et al, 2016;Paula et al, 2014), correlate the general processes governed by microbes (such as soil respiration, microbial biomass or microbial enzyme activities) with detailed surveys of plant communities (Purahong et al, 2016;Strecker, González Macé, Scheu, & Eisenhauer, 2016) or infer microbial diversity indirectly from the physiological profiling of soil samples ("functional diversity"), rather than determining taxonomic diversity directly via genetic analysis (Araya, Bartelheimer, Valle, Crujeiras, & García-Baquero, 2017;Klimek, Chodak, Jaźwa, & Niklińska, 2016;Klimek et al, 2015;Markowicz, Woźniak, Borymski, Piotrowska-Seget, & Chmura, 2015;Mureva & Ward, 2017). The responses of microbial functional and taxonomic diversities to changes in plant productivity are not directly comparable (Zhang, Johnston, Barberán, Ren, & Lü, 2017) and likely reflect the operation of different processes.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, Courty et al (2010) demonstrated that Populus genotypes with varying rates of mycorrhizal colonization produced different amounts of the enzymes involved in nutrient mobilization. Moreover, Purahong et al (2016) demonstrated that, together with soil pH and water content, one-third of the overall patterns of soil enzymes could be explained by tree species identity and genotypic diversity. Trees have a major effect on seasonal resource availability as a result of the litter fall in autumn and belowground carbon exudation and nutrient uptake during the growing season (Kaiser et al, 2010;Šnajdr et al, 2011); therefore, seasonality and tree phenology may influence the quality and quantity of organic inputs in soil (Šnajdr et al, 2011).…”
Section: Introductionmentioning
confidence: 99%